The place of translation in the 21st century English teaching-learning - Selhorst, Lucas Alves (BELT - Brazilian English Language Teaching Journal, 2021)
Despite the criticisms that can be made of the use of translation in teaching and learning English, it is still widely used, in different ways. Recognizing the controversies of this theme, this bibliographic research aims to understand the place of translation in the 21st century English teaching-learning process. In addition to books and scientific papers, we also sought to look at the National Common Curricular Base (BNCC), since this is the most recent normative document for the development of curricula and pedagogical proposals in Brazil. Translation as a method presents weaknesses, considering that the ability of the methods to be adequate in the face of the challenges that are being posed has been questioned, this, the oldest, can be seen as a legacy that no longer makes sense. As a resource, it was found that the translation is in a better situation. Being able to collaborate for the English language learning, for the development of linguistic perceptions, and of the awareness that involves several aspects of the English language, as well as the mother tongue, as long as it is thought of as a significant, current, contextualized resource that takes into account the particularities and needs of students.